1994
DOI: 10.1080/00927879408825115
|View full text |Cite
|
Sign up to set email alerts
|

Ga actions on Cn

Abstract: Rational actions of the additive group of complex numbers on complex n space are considered. A ring theoretic criterion for properness is given, along with ideal theoretic criteria for local triviality of such actions. The relationship between local triviality and flatness of the polynomial ring over its subring of G, invariants is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…It was proved in [ 1 ] that o is proper if and only if ö is surjective, and locally trivial if and only if im(<5) n C[X]Ga generates the unit ideal in C[X]. In the latter case the action admits a quasiaffine geometric quotient.…”
Section: Proper Algebraic Actions On C"mentioning
confidence: 99%
See 2 more Smart Citations
“…It was proved in [ 1 ] that o is proper if and only if ö is surjective, and locally trivial if and only if im(<5) n C[X]Ga generates the unit ideal in C[X]. In the latter case the action admits a quasiaffine geometric quotient.…”
Section: Proper Algebraic Actions On C"mentioning
confidence: 99%
“…An easy consequence of the surjectivity of ô is the absence of fixed points. Moreover, for proper Ga actions we have shown that the action is locally trivial if and only if the ring extension QX]01" «-» C[X] is flat, and equivariantly trivial if and only if the extension is faithfully flat [1]. If there is a slice for the action, i.e.…”
Section: Proper Algebraic Actions On C"mentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown [2] that C 0 is finitely generated for any triangular action on C 4 . In the special case under consideration, we show that Y ∼ = Spec C 0 .…”
Section: Locally Trivial Triangular Actions On Cmentioning
confidence: 99%
“…In the special case where X = C n and the dimension of U is at least n − 2, a famous result of Miyanishi [10,Theorem 4] gives the requisite condition on the ring of invariants. For n = 3, U = G a , and the action proper, an Euler characteristic argument shows that the action is not merely locally trivial, but in fact conjugate to a translation [4]. Fauntleroy and Magid prove in [6] that a free G a action on any factorial quasiaffine surface is conjugate to a translation.…”
Section: Introductionmentioning
confidence: 99%